(untitled) (KULT_online, 2012)
Word is that academic reflections on (historic) events are dependent on a certain time displacement. By now, the terror attacks of 11 September 2001 date back one decade. For the longest time, concern and traumatic memories had a strong effect upon academic discourses on 9/11. Birgit Däwe’s Ground Zero Fiction and the compendium Learning 9/11 edited by Irina Bauder-Begerow and Stefanie Schäfer are distinctive for a shift in perspective. The systematization of literary responses to 9/11 replaces content-driven analyses of individual writings. The focus on the didactic mediation of the attacks to those generations who have no active memory of them whatsoever transforms and relativizes the question of 9/11’s political and societal impact. Both volumes add to the canon of 9/11 literature, yet at the same time they could be read as the beginning of the end to the rampant growth of writings on 9/11.